Differences in efficiency among Kansas beef cow producers - S. Eidson; Michael R. Langemeier; R. Jones (Kansas Agricultural Experiment Station Research Reports, 1998)
Beef cow producers must manage costs of production and improve production efficiency to compete with hog and poultry and other beef cattle producers. A sample of 46 beef cow enterprises from the Kansas Farm Management database was used to measure technical, economic, and overall efficiencies. On average the farms were 92% technically efficient, 80% economically efficient and 73% overall efficient. Our results suggest that 5% increases in economic and scale efficiencies would increase profit per cow by 20 and 24, respectively.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; Cows; Efficiency; Profitability